2018
DOI: 10.1007/s12035-018-0999-7
|View full text |Cite
|
Sign up to set email alerts
|

Increased ROS Level in Spinal Cord of Wobbler Mice due to Nmnat2 Downregulation

Abstract: Amyotrophic lateral sclerosis is a devastating motor neuron disease and to this day not curable. While 5-10% of patients inherit the disease (familiar ALS), up to 95% of patients are diagnosed with the sporadic form (sALS). ALS is characterized by the degeneration of upper motor neurons in the cerebral cortex and of lower motor neurons in the brainstem and spinal cord. The wobbler mouse resembles almost all phenotypical hallmarks of human sALS patients and is therefore an excellent motor neuron disease model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 61 publications
0
33
1
Order By: Relevance
“…As the coenzyme NAD + was found to be significantly downregulated in the spinal cord of wobbler animals [ 18 ], we aimed to investigate the effect of a NAD + boost on the motor neuronal development. The investigations were equally performed with two developmental stages (p20, p40).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As the coenzyme NAD + was found to be significantly downregulated in the spinal cord of wobbler animals [ 18 ], we aimed to investigate the effect of a NAD + boost on the motor neuronal development. The investigations were equally performed with two developmental stages (p20, p40).…”
Section: Resultsmentioning
confidence: 99%
“…Since the Nmnat2 level was proven to show a significant downregulation in the spinal cord of wobbler mice [ 18 ], we aimed to study the effect of an elevation of the Nmnat2 level on motor neuronal integrity in vitro. Since Ali and coworkers have shown that caffeine is able to increase the Nmnat2 level in cortical neurons in vitro [ 25 ], we used this compound as treatment of our cell culture.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations